Risk factors for mortality among eclamptics admitted to the surgical intensive care unit at Tikur Anbessa Hospital, Addis Ababa, Ethiopia - berihun, Eyob; Gaym, Ashebir (Ethiopian Journal of Reproductive Health, 2018)
Abstract Background: Facilities for intensive care are scarce in low-resource settings. Identifying determinants of mortality among eclamptics requiring intensive care will provide insight regarding prioritization as to which group of eclamptics would benefit from earlier referral or transfer to ICU this will improve survival in the face of scarce resources available for ICU. Setting: Tikur Anbessa Hospital, a teaching and central referral hospital in Addis Ababa, Ethiopia. Objectives: To identify risk factors associated with mortality of eclamptics who required intensive care after admission to TAH- SICU. Methods: A ten years retrospective, hospital based case-control study. The case records of eclamptics admitted to the SICU during the study period were reviewed. Cases were those mothers who died, with the survivors acting as controls. Several variables were assessed among the cases and controls to assess their risk towards mortality; OR and 95% CI computed. Results: The majority were below the age of 30 years, 124 (84.4%); nulliparous 103 (70.1%) and from Addis 113 (76.9%). Lateralizing signs were observed in 11(7.5%). Age greater than 29 years (OR 3.29; 95% CI, 1.18-9.12); being a housemaid (OR 5.93; 95% CI, 1.13-34.15); multiparity (OR 3.32, 95% CI 1.40-7.87) and the presence of lateralizing signs at admission (OR 4.57; 95% CI, 1.12-19.04) were significantly associated with the risk of mortality. The overall SICU case fatality rate was 25.9 %. Conclusion: More vigilant attention should be given to eclamptics older than 29 years, those with low-socioeconomic status, multiparous mothers and presence of lateralizing signs at admission. Prioritizing ICU admission to these groups may improve survival. There is a need to conduct more studies on ICU mortality to come up with more detailed indications for prioritizing ICU admission. (Ethiop. J.Repr. Health .May 2007, 1(1):4-16) 1. Ghandi Memorial Hospital, Addis Ababa, Ethiopia. 2. Department of Obstetrics and Gynecology